The role of neuropeptides in learning: Insights from C. elegans. (August 2020) - De Fruyt, Nathan; Yu, Alex J.; Rankin, Catharine H.; Beets, Isabel; Chew, Yee Lian
Graphical abstract: Abstract: Learning is critical for survival as it provides the capacity to adapt to a changing environment. At the molecular and cellular level, learning leads to alterations within neural circuits that include synaptic rewiring and synaptic plasticity. These changes are mediated by signalling molecules known as neuromodulators. One such class of neuromodulators are neuropeptides, a diverse group of short peptides that primarily act through G protein-coupled receptors. There has been substantial progress in recent years on dissecting the role of neuropeptides in learning circuits using compact yet powerful invertebrate model systems. We will focus on insights gained using the nematode Caenorhabditis elegans, with its unparalleled genetic tractability, compact nervous system of ∼300 neurons, high level of conservation with mammalian systems and amenability to a suite of behavioural analyses. Specifically, we will summarise recent discoveries in C. elegans on the role of neuropeptides in non-associative and associative learning.